Being the Church for Others: A critical analysis of John W. de Gruchy’s contextual ecclesiology of engagement - Menard, Wayne (Université Saint-Paul / Saint Paul University, 2016)
This thesis examines the contextual theology of John W. de Gruchy whose critique of the Dutch Reformed Church’s (DRC) iteration of a Reformed theology in support of apartheid, provided a theological cantus firmus for the church struggle against apartheid. There are two questions that guide this thesis. The first question I ask is, ‘Why, in 1986, did the Dutch Reformed Church recant its pro-apartheid stance which it had maintained, both officially and unofficially for one hundred and thirty-nine years?’ The second question concerns John W. de Gruchy in his capacity as a leading theologian in the Christian church and as a representative of the Reformed tradition in South Africa. I ask, ‘What was his role in the dismantling of the social experiment called apartheid?’ Drawing upon de Gruchy’s theological literature, written over the past fifty years, an argument is crafted suggesting that, by answering the second question, we also answer the first. To this end, a brief account of the Afrikaner rise to political and theological dominance in South Africa is provided with a view to establishing the social, political and economic context.
Keywords: de Gruchy; South Africa; apartheid; theology; Reformed theology; liberation theology; contextual theology